LOCAL LIMPHOCYTIC REGULATION OF HEMATOPOETIC TISSUE RECOVERY OF IRRADIATED RECIPIENTS AFTER INJECTION OF THE MYELOTRANSPLANT AT THE LEVEL OF THEIR BONE MARROW - Popov, N.N.; Romanova, E.A.; Lavelin, S.B. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
High supression of proliferation of simulated splenocyts by bone marrow lymphocytes in vitro which appeared on the 30 day of the study was noted after the total irradiation of (CBAxC57BL)F1 mice in the dose 9 Gy and following the syngenic mielo- and lymphomielotransplant injections. More manifested suppressory activity was observed in the lymphocytes of the animals, injected with a combined transplant as compared to the cells of the animals, injected with myelocaryocytes per se. A phenotypic study of the bone marrow cells has shown that the T-depleted fraction lymphocytes, which expressed sIg-molecules and cells, characterised by a phenotype of the zero-lymphocytes, exibits suppressory properties.